(untitled) (Journal of Nepal Physical Society, 2021)
The structural, electronic, and magnetic properties of vacancy structures with triangular shape are related to the defect in single hexagonal boron nitride (h-BN) sheet. It is investigated by using density functional theory calculations. The first-principles calculations based GGA functionals have been implemented to study the structural, electronic and magnetic properties of pure and defected hexagonal boron nitride (h-BN) monolayer sheet using Quantum ESPRESSO (QE) package, 6.5 version. The calculated values of formation energy reveal the structural stability of the defected systems. The formation energies for B and N vacant system are found to be 16.45 eV and 12.87 eV respectively. This predicts that the N vacant system is more preferable with lower formation energy. The defect in h-BN seems to be changing its band gap and magnetic properties of h-BN system. The 6.25 % B-vacancy results h-BN to be half metallic ferromagnetic with total magnetization of 2.74µB/cell. Further, 6.25 % N-vacancy causes it to be magnetic semiconductor with total magnetization 1.00µB /cell.